Charakterisierung von Immunseren durch Bindung von monovalentem Penicilloylhapten - U. Otz; C.H. Schneider; A.L. de Weck (CHIMIA)
The preparation of tritium-labeled Nβ-benzylpenicilloylalanine and its use as a monovalent hapten in binding studies is described. The binding of 10-8M hapten to antisera of various species is readily performed but insufficient test sensitivity hampers some potential applications. N-Benzylpenicilloyl-tyramine- J125 is another BPO-hapten of ready availability. Its binding capacity could however not be established thus far.